An Evaluation on Eastern Anatolia Late Iron Age (Persian/Achaemenid Period). - TOSUN, Murat; PARLITI, Umut; CANER, Eyüp (Arkeoloji Dergisi, 2021)
Very few studies have been carried out on the cultural phase of the Persian/Achaemenid Period known as Late Iron Age in Eastern Anatolia Region and a small number of archaeological findings have been obtained. Before the Persian/Achaemenid Period in the Eastern Anatolia Region, Urartu was the most culturally profound kingdom of the region in every sense. However, in the light of excavations carried out in Eastern Anatolia, the collapse of the Kingdom of Urartu may have created a hiatus (gap) situation in almost the whole region. This situation has been changing with the ceramic data and carbon analysis and the data reveal that there was a return to the old settlement areas at the end of 5th century BC and early 4th century BC. All these facts probably point out that a new cultural formation process started in the later phase of the Persian / Achaemenid Period in the Eastern Anatolia Region and that people began to live in rural areas (such as Sazlıkyanı Höyük) rather than central areas. Although there had been a return to the old central settlements since the end of the 5th century BC, it is understood that the rural life tradition continued, as the settlement seen in these centers can only be determined archaeologically considering the weak data.